A Fully-Adaptive Threshold Partially-Oblivious PRF - Baecker, Ruben; Gerhart, Paul; Rausch, Daniel; Schröder, Dominique (Lecture Notes in Computer Science, 2025)
Oblivious Pseudorandom Functions (OPRFs) are fundamental cryptographic primitives essential for privacy-enhancing technologies such as private set intersection, oblivious keyword search, and password-based authentication protocols. We present the first fully adaptive, partially oblivious threshold pseudorandom function that supports proactive key refresh and provides composable security under the One-More Gap Diffie-Hellman assumption in the random oracle model. Our construction is secure with respect to a new ideal functionality for OPRFs that addresses three critical shortcomings of previous models–specifically, key refresh and non-verifiability issues that rendered them unrealizable. In addition, we identify a gap in a prior work’s proof of partial obliviousness and develop a novel proof technique to salvage their scheme.
CRIS-Team Scopus Importer:2025-09-05
Keywords: Adaptive Security; Partially-Oblivious PRF; Threshold Cryptography; Universal Composability